Peran Guru PAI dalam Pembinaan Karakter Religius Peserta Didik melalui Kegiatan Mentoring di SDIT Al Irsyad Al Islamiyyah Karawang - Solihat, Dewi; Wahyudi, Undang Ruslan (Lembaga Yasin AlSys, 2023)
Religious character is a character that shows obedient attitudes and behavior in carrying out the teachings of the religion they adhere to. Manifested in the form of the quality and quantity of his relationship with God, fellow human beings and also the environment that has been internalized within himself. This study aims to describe the efforts of PAI teachers in fostering the religious character of students at SDIT Al Irsyad Al Islamiyyah Karawang through mentoring activities. The approach in this study uses a qualitative descriptive approach. The subjects of this study were PAI teachers and students. From the research results, the mentoring activities implemented at SDIT Al Irsyad Al Islamiyyah Karawang are very effective as one of the efforts in forming the religious character of students. Because in mentoring, students are taught good etiquette, namely etiquette towards parents, etiquette towards teachers, etiquette towards friends, etiquette towards oneself, etiquette towards the environment, etiquette in dressing, etiquette towards knowledge, etiquette in eating and drinking. The teacher's role in mentoring activities is teaching material and overseeing religious habituation in schools. The obstacles in this mentoring activity are the lack of time intensity, teacher competence and lack of support from students' parents.